2011
DOI: 10.1007/s00256-011-1303-3
|View full text |Cite
|
Sign up to set email alerts
|

Double-bundle depiction of the anterior cruciate ligament at 3 Tesla

Abstract: The double-bundle anatomy of the ACL is visualized in 94% of patients on 3T MRI. Because of potentially associated clinical benefits, we advocate to report separately on the anteromedial bundle and posterolateral bundle in case of anterior cruciate ligament injury of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Kaya et al (2010) reported the identification rate of 42.2% using 1.5T-MRI. On the other hand, Adriaensen et al (2012) reported the double-bundle identification rate of 94% using 3T-MRI. They described that magnetic field strength of MRI may have affected the results of their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kaya et al (2010) reported the identification rate of 42.2% using 1.5T-MRI. On the other hand, Adriaensen et al (2012) reported the double-bundle identification rate of 94% using 3T-MRI. They described that magnetic field strength of MRI may have affected the results of their study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the previous studies have examined on this matter, it is still controversial regarding which plane is better depicted (Steckel et al, 2007;Kwon et al, 2009;Kaya et al, 2010;Adriaensen et al, 2012;Mackay et al, 2014). Adriaensen et al (2012) studied 50 knees in the standard planes using 3T-MRI and reported that the double-bundle ACL was identifiable in 47 knees (94%). The plane in which the bundles were best visualized was the ACL axial plane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both contribute substantially to the anterior and rotational stability of the knee. The AM bundle is inserted more anteromedially on the tibia and originates more proximally on the femur than the PL bundle (345). The two bundles run parallel on knee extension during which the AM bundle loosens and the PL bundle tightens; and cross on knee flexion, when the AM bundle tightens and the PL bundle loosens (Fig.…”
Section: Surgical Techniques and Surgical Navigation Terminologymentioning
confidence: 99%